URGENSI PENDIDIKAN KARAKTER (Kajian Filsafat Pendidikan) - Putra Aryana, I Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This article aims to examine the importance of character education to create Indonesian people who have knowledge, have noble morals, have personality and character. The writing of this article uses the librarian method and in-depth study of the literature. The issue of the character of students and the character of the nation is currently the most important issue for the world of education in the country. Education includes two main interests, namely the development of individual potential and the inheritance of cultural values. There are three foundations that make up the philosophy of education, namely: the ontological, epistemological and axiological foundation. A person who is studying education is required to think about essential problems regarding education. Various problems of the nation today can only be fixed by individuals of the younger generation with character: smart, quality, ethical, disciplined, honest, hard work and moral. It is hoped that the development of Indonesia's young generation can become the identity of the nation's children in the era of globalization and acculturation of world culture, and can encourage independence in an effort to increase the competitiveness of Indonesia's young generation. The back and forth of the nation's future is very much determined by the quality of human resources who are intelligent, have character, have good character, in accordance with the philosophy and goals of national education.